Flexible inflation targets, forex interventions and exchange rate volatility in emerging countries - Juan Carlos Berganza; Carmen Broto (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
Emerging economies with inflation targets (IT) face a dilemma between fulflling the theoretical conditions of "strict IT", which implies a fully flexible exchange rate, or applying a "flexible IT", which entails a de facto managed floating exchange rate with forex interventions to moderate exchange rate volatility. Using a panel data model for 37 countries we find that, although IT lead to higher exchange rate instability than alternative regimes, forex interventions in some IT countries have been more effective in reducing volatility than in non-IT countries, which may justify the use of "flexible IT" by policymakers.
URN:NBN:fi:bof-201408072056
Keywords: E31; E42; E52; E58; F31; 330; Inflation targeting; Exchange rate volatility; Foreign exchange interventions; Emerging economies